Internal bracing with suture tape augmentation reduces positive postoperative pivot shift in patients with anterior cruciate ligament reconstructions - Simone Elmholt; Torsten Nielsen; Anders Galaly; Mogens Strange; Kaspar Saxtrup; Martin Lind (Journal of Experimental Orthopaedics)
Abstract Purpose In biomechanical testing synthetic ligament augmentation demonstrated improved graft strength, which may lead to improved clinical outcomes. Therefore, this study aimed to investigate whether this procedure would improve clinical outcomes, compared to conventional anterior cruciate ligament reconstruction (ACLR). Methods This study was a retrospective register‐based cohort study. Data were obtained from a single clinic (Silkeborg Regional Hospital, Denmark). A cohort of patients undergoing ACLR with either hamstring or quadriceps tendon autografts in combination with an InternalBrace was identified. Using propensity scoring, the InternalBrace group was matched 1:1 to a control group of ACLR patients without augmentation from the same clinic. The primary outcome was sagittal knee laxity, and secondary outcomes were rotational stability (pivot shift), patient‐reported outcome measures (PROMs) with the Knee Injury and Osteoarthritis Outcome Score (KOOS) and revision surgery rates. Results A total of 324 patients were included, 162 in each group. At 1‐year follow‐up the InternalBrace group demonstrated similar sagittal knee laxity of 2.2 mm (95% CI: 1.9–2.4 mm) compared to 1.9 mm in the control group (95% CI: 1.6–2.1 mm) (p > 0.05). The InternalBrace group demonstrated a statistically significant lower risk of having a positive pivot shift at the 1‐year follow‐up: 18% versus 30% (p < 0.01). There were no differences between the groups in the KOOS subcategories (p > 0.05 for all comparisons). At 2‐year follow‐up, two patients had a revision surgery in the InternalBrace group compared to three patients in the control group (p = 0.3). Conclusion Compared to conventional ACLR, InternalBrace reduces the risk of having a positive pivot shift 1 year postoperatively and demonstrates similar outcomes regarding sagittal knee laxity, revision rates and PROMS. Therefore, this study concludes that InternalBrace are safe to use in ACLR. Level of Evidence Level III.